Pola Tata Ruang Rumah Pengusaha Genteng di Desa Wirun Mojolaban Sukoharjo - Agung Kumoro Wahyowibowo; Kahar Sunoko; Musyawaroh Musyawaroh (Universitas Sebelas Maret Surakarta, 2025)
Houses often develop to fulfill the biological, psychological, social, and economic needs of families, and even function as production and business spaces. Houses owned by roof tile entrepreneurs in Wirun Village, Mojolaban, Sukoharjo, show diverse spatial patterns as a result of the combination of residential and business activities. This research aims to identify the influence of residential and business processes on the spatial arrangement of houses. The research used a qualitative descriptive method through field observation and interviews with categorization. The results showed that the spatial arrangement of roof tile entrepreneurs' houses prioritizes the production process. Most of the house area is used for business, especially roof tile production activities. The building facade is designed to support the loading and unloading process. The circulation pattern is mainly determined by the needs of roof tile production. Therefore, the spatial arrangement is more business-oriented, reflecting the integration between residential space and economic activities in the house.